The Global Financial Crisis, Austerity, and Mental Health: The Case of Walker’s Wisconsin - (:unkn) unknown (My University, 2020)
A case study of health care in Wisconsin under Governor Walker is presented in order to explore some effects of austerity in the United States. The case study follows the trajectory of rhetoric employed by the Walker campaign, linking it to policy changes and subsequent health outcomes for people in the state. I argue that, despite Walker’s proposal for funding mental health, the trajectory of mental health services in Wisconsin is toward increased constriction of public services. Additionally, Walker is able to both endorse individual agency and simultaneously promote policies that restrict it through a politics of need (Robertson 1998:1421). In the case of Walker’s Wisconsin, the politics of need works to hide cuts to services for the poorest people in Wisconsin by appealing to American ideals of individualism.
Keywords: mental health; structural violence; politics of need; Medicaid; Affordable Care Act